Phenomenology of fiscal consciousness: A philosophical inquiry into narratives and ethics of taxation in the Indonesian Stock Exchange (2004–2024) - Apollo, Apollo (PT Aksara Indo Rajawali, 2025)
This study introduces the Phenomenology of Fiscal Consciousness (PFC) as a framework for interpreting taxation in the Indonesian Stock Exchange (IDX, 2004–2024) beyond economic rationality, emphasizing existential, ethical, and spiritual dimensions. The dataset includes 22 audit reports on tax-related fraud, covering two pharmaceutical firms, two telecommunications companies, two aviation corporations, two insurance and investment SOEs, two construction firms, two property developers, one state-owned steel manufacturer, and 9 cases in food, manufacturing, and mixed enterprises. Additionally, 21 semi-structured interviews with auditors, regulators, investors, consultants, and journalists, along with corporate ESG and sustainability reports, were analyzed. Cases and participants were selected based on their regulatory significance, ethical relevance, and sectoral diversity. The study applies phenomenological reduction (epoché) to suspend positivist assumptions and reveal lived experiences of fiscal responsibility. Rigor is reinforced through triangulation of documents, narratives, and interviews, integrating Western phenomenology with Eastern mindfulness ethics. Findings show three constellations: (1) legality versus legitimacy, where audit texts convey symbolic suspicion; (2) taxpayer consciousness as a moral-symbolic formation shaped by guilt and responsibility; and (3) spiritualization of fiscal narratives through ESG discourse, reframing compliance as mindful care and interbeing. PFC reimagines taxation not as a legal compulsion but as an embodied, intersubjective, and ethical-spiritual practice.